Upaya meningkatkan kemampuan motorik halus melalui membatik pada anak kelompok B di BA Aisyiyah Wonosari tahun ajaran 2015/2016 - Dwi Larasati, Athien Fadwa, Drs. Ilham Sunaryo, M.Pd AUD, Wili Astuti, S.Pd., M.Hum (2015)
The purpose of this research is to increase children fine motor skills at group B in BA AisyiyahWonosari, Bendungan, SimoSubdistrict, Boyolali Regency 2015/2015 academic year with through batik. The research is a classroom action research. The subjects of are students 5-6 years old in BA AisyiyahWonosari, Bendungan, SimoSubdistrict, Boyolali Regency learn year 2015/2016 that't amounts 10 children, a consist of 5 boys and 5 girls. The research is done in two cycle procedures which consist of four steps: planning, implementation, observasion and reflection. The data children fine motor skills collected by observation method, field notes and interview. The analysis technical use include technic analysis comparative. Before the action cycle result obtained cycle reaches 52.18%. First cycle reaches 68.43%, and second cycle reaches 86.56%.The study states that there are significant differences between the results of the fine motor skills of children in pre-cycle, first cycle and second cycle by using the through batik method that can improve fine motor skills of children group B in BA AisyiyahWonosari, Bendungan, Simo, Boyolali. The result of this research is there is an increase of the fine motor skills in children through batik group B in BA AisyiyahWonosari the academic year 2015/2016.